THE INFLUENCE OF PRODUCT QUALITY, WOM, AND PRICE PERCEPTION ON PURCHASING DECISIONS - Dewi Yunitaningrum; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This thesis employs quantitative research to examine whether product quality, WOM, and price perception individually and simultaneously influence purchasing decisions at Thrifturbae.id Surabaya. A descriptive quantitative method was used with a sample of 80 respondents, determined by probability sampling. Data were collected via questionnaires using a Likert scale. Validity, reliability, classical assumption, multiple linear regression, T (partial), and F (simultaneous) tests were conducted. Results show that product quality, WOM, and price perception simultaneously affect purchasing decisions. However, product quality has no significant individual effect, while WOM and price perception do.